Trait Anxiety Does Not Predict the Anxiogenic Response to Sleep Deprivation - Sundelin, Tina; Holding, Benjamin C. (Frontiers in Behavioral Neuroscience, 2022)
Sleep deprivation has in several studies been found to increase anxiety. However, the extent to which this anxiogenic effect depends on one’s underlying trait anxiety has not previously been determined. Using two separate sleep-loss experiments, the current research investigated whether trait anxiety (STAI-T) moderates the increase in state anxiety (STAI-S) following one night of total sleep loss (study 1, N = 182, age 25.3 ± 6.5, 103 women) and two nights of partial sleep restriction (study 2, N = 67, age 26.5 ± 7.4, 38 women). Both studies showed the expected anxiogenic effect of sleep loss, and a clear relationship between trait anxiety and state anxiety. However, the anxiogenic effect of sleep loss was not moderated by trait anxiety, as there was an equal impact regardless of trait anxiety level. These findings indicate that, although sleep loss is related to general anxiety as well as anxiety disorders, for a non-clinical sample the anxiogenic effect of short-term sleep loss is not affected by baseline levels of anxiety.